PENGARUH TEMPERATUR DAN TEKANAN TERHADAP HASIL CETAKAN POLYPROPYLENE MENGGUNAKAN MESIN INJECTION MOLDING VERTIKAL: The Influence of Temperature and Pressure on the Results of Polypropylene Molding Using a Vertical injection Molding Machine - Sugiyanto, Didik; Chan, Yefri; Taopik, Angga (Universitas Negeri Jakarta, 2023)
Currently, the use of plastic products is increasing in various fields, due to their flexibility and low production costs. The injection molding process is a technique that is often used in the formation of plastic products. The focus of the problem of this study is the effect of heating temperature and hydraulic pressure on the results of box and gear molds using the injection molding process. The test method uses variations in temperature and hydraulic pressure to produce the maximum mold shape in the box and gear. From the results of the injection molding test for full yield gear products with a melt temperature of 368ºC, a mold temperature of 40ºC, and an injection pressure of 490 Psi, there was a failure in the test results due to the release of liquid which did not come out directly to fill the mold, because the pressure from the hydraulic jack must gradually.